A NEW POROLEPIFORM CROSSOPTERYGIAN SPECIES FROM THE MIDDLE DEVONIAN OF THE LENINGRAD REGION - Vorobyeva E.I.; Kanyukin A.A. (My University, 2004)
A new species of porolepiform crossopterygians Glyptolepis? nessovi sp. nov. from the Middle Devonian (Eifelian Stage, Aruküla Regional Stage) of the Leningrad Region is established. The anterior part of the ethmosphenoid, the clavicle fragment, and scales are described. Morphologically, this species is close, in some respects, to Paraglyptolepis karksiensis Vorobyeva from the Middle Devonian of Estonia.
Keywords: porolepiform crossopterygians; Paleozoic::Devonian::Middle::Eifelian; Палеозой::Девонская::Средний::Эйфельский